(untitled) (Journal of the College of Basic Education, 2022)
It has been shown through the research that the use of the method of biological reclamation of soil affected by salts (in the district of Al-Khairat in Karbala Governorate) has positively affected the physical and chemical properties of the soil and led to an increase in its productive value, as the technique of bio-reclamation (vegetative) can be performed on site without the need To a large amount of water to wash the soil from salts, in addition to the decrease in its economic cost, as the soil of the study area was transformed from a non-alkaline saline soil before reclamation to a non-saline alkaline soil after reclamation, according to the standard of the internationally accredited American salinity laboratory. The study also reached many results, the most important of which was a decrease in Electrical conductivity, basicity, acidity, positive and negative ions,